PENINGKATAN KETERAMPILAN MEMBACA CEPAT MELALUI TEKNIK SKIMMING PADA SISWA KELAS V SEKOLAH DASAR - Anni Gultom; Maria Friska Nainggolan (Fakultas Ilmu Pendidikan Universitas Sari Mutiara Indonesia, 2019)
This research is Classroom Action Research (CAR). This Classroom Action Research was carried out in two cycles, each cycle consisting of two shelves, namely planning, action, observation, and reflection. Each cycle consists of 2 meetings. Data collection instruments used in this study were observation sheets and tests. Observation Sheets are used to study the activities of students and teachers in the learning process. While the test is conducted at the end of each cycle to learn the improvement of speed reading skills with skimming techniques. Based on the results of observations of learning both in cycle I and cycle II students have learned in accordance with the stages of learning undertaken. In general, based on the results and observations made, the results obtained show an increase in the value of skills in each cycle. Through these results it can be concluded that the skimming technique can improve the speed reading skills of fifth grade students .